Evaluation of behavioural and antioxidant activity of Cytisus scoparius Link in rats exposed to chronic unpredictable mild stress - Harisudhan Thanukrishnan; Babu Chidambaram; Nirmal Jayabalan; Ramanathan Muthiah (BMC, 2008)
Abstract Background Various human diseases have oxidative stress as one of their component. Many herbs have been reported to exhibit properties that combat oxidative stress through their active constituents such as flavonoids, tannins, phenolic compounds etc. Cytisus scoparius (CS) Link, (Family: Leguminosae), also called Sarothamnus scoparius, has been shown in invitro experiments to be endowed with anti-diabetic, hypnotic and sedative and antioxidant activity. Therefore this study was carried out to evaluate CS for its anxiolytic, antidepressant and anti-oxidant activity in stressed rats. Methods 60% methanolic extract of CS was quantified for phenolic content by Folin-Ciocalteau's method. Chronic unpredictable mild stress (CMS) was employed to induce stress in rats. CS (125 and 250 mg/kg, p.o) and diazepam (DZM) (2 mg/kg, p.o) was administered during the 21 day stress exposure period. Anxiolytic and antidepressant activities of CS were assessed in open field exploratory and behavioural despair paradigms, respectively. Plasma glucose and total lipids; endogenous antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT); non-enzymic-ascorbic acid and thiobarbituric acid reactive substances (TBARS) levels were measured in brain, kidneys and adrenals using standard protocols to assess the effect of CS. Results Total phenolic content of CS was found to be 8.54 ± 0.16% w/w. CMS produced anxiogenic and depressive behaviour in experimental rats with metabolic disturbance. Significant decrease in SOD, CAT levels and increase in lipid peroxidation level was observed in stressed rats. CS administration for 21 days during stress exposure significantly increased the ambulatory behaviour and decreased the freezing time in open field behaviour. In behavioural despair test no significant alteration in the immobility period was observed. CS also improved SOD, CAT, and ascorbic acid level and controlled the lipid peroxidation in different tissues. Conclusion CS possesses anti-stress and moderate anxiolytic activity which may be due, in part, to its antioxidant effect that might warrant further studies.